A randomized-controlled clinical trial comparing the effects of steroid phonophoresis and therapeutic ultrasound in carpal tunnel syndrome - Burcu Ortanca,; Onur Armağan,; Fulya Bakılan,; Merih Özgen,; Funda Berkan,; Setenay Öner, (Archives of Rheumatology, 2022)
Objectives: In this study, we aimed to compare the efficacy of ultrasonography (US) and steroid phonophoresis (PH) treatments in patients with idiopathic carpal tunnel syndrome (CTS). Patients and methods: Between January 2013 and May 2015, a total of 46 hands of 27 patients (5 males, 22 females; mean age: 47.3+13.7 years; range, 23 to 67 years) with idiopathic mild/moderate CTS without tenor atrophy or spontaneous activity in abductor pollicis brevis were included. The patients were randomly divided into three groups. The first group was ultrasound (US) group, the second group was PH group, and the third group was placebo US group. Continuous US with a frequency of 1 MHz, an intensity of 1.0 W/cm2 was used in the US and the PH groups. The PH group received 0.1% dexamethasone. Placebo group received a frequency of 0 MHz, an intensity of 0 W/cm2 US. Treatments were administered for five days a week, a total of 10 sessions. All patients also wore night splints during treatment. The Visual Analog Scale (VAS), Boston Carpal Tunnel Questionnaire consisting of two parts, namely the Symptom Severity Scale and Functional Status Scale), grip strength, and electroneurophysiological evaluations were compared before the treatment, after the treatment, and three months later. Results: All clinical parameters improved in all groups after treatment and at three months, except for the grip strength. Recovery in the sensory nerve conduction velocity between palm and wrist was seen in US group at three months after the treatment; however, recovery in the sensory nerve distal latency between the second finger and palm was seen in PH and placebo groups after treatment and at three months after the treatment. Conclusion: The results of this study suggest that splinting therapy combined with steroid PH, placebo or continuous US is effective for both clinical and electroneurophysiological improvement; however, electroneurophysiological improvement is limited.